Radiofrequency denervation of renal arteries. Myth or reality? - V A Grigin; N M Danilov; Yu G Matchin; I E Chazova (Системные гипертензии, 2015)
Resistant hypertension is an urgent problem in modern cardiology, leading to myocardial infarction, stroke, and, as a consequence, early disability of patients. The emergence of such a method as radiofrequency denervation of the renal arteries in the complex antihypertensive therapy can expect to achieve control of blood pressure and thus reduce the risk of cardiovascular complications. This article presents the current state of the use of this method in clinical practice.